2009
DOI: 10.4110/in.2009.9.5.158
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Therapy Applying Membrane-bound Form of Cytokines

Abstract: Tumor therapy using cytokines has been developed for last two decades. Several recombinant cytokines and tumor cell vaccines produced by cytokine gene transfer have been in clinical trials, but several side effects hamper routine clinical applications. Many cytokines are originally expressed as membrane-bound form and then processed to secretory form exerting paracrine effects. Though functional differences of these two types of cytokines are elusive yet, the membrane-bound form of cytokine may exert its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
1
13
1
Order By: Relevance
“…4C) priming. 42 In our study, CD8 + T cells were activated by MethA tumor cells expressing mbIL-12p35, indicating that the mbIL12p35 molecules on the MethA tumor cells provide a costimulatory signal for direct priming of CD8 + T cells. In contrast, Nagarajan and Selvaraj 40 reported that GPI-anchored IL-12 p35 on CHOK1 cells did not stimulate PHA-activated human T cells.…”
Section: Discussionsupporting
confidence: 50%
“…4C) priming. 42 In our study, CD8 + T cells were activated by MethA tumor cells expressing mbIL-12p35, indicating that the mbIL12p35 molecules on the MethA tumor cells provide a costimulatory signal for direct priming of CD8 + T cells. In contrast, Nagarajan and Selvaraj 40 reported that GPI-anchored IL-12 p35 on CHOK1 cells did not stimulate PHA-activated human T cells.…”
Section: Discussionsupporting
confidence: 50%
“…Membrane bound cytokines (45, 46) offer an attractive approach for delivering a desired cytokine to the immediate microenvironment of the T cell-aAPC synapse along with alleviating the need to add the soluble (expensive) cytokine to the culture system and avoiding the need for a clinical-grade cytokine for clinical applications. Membrane-bound IL-15 has been used to propagate T cells (6, 47) and NK cells (48, 49) on aAPC derived from K562 cells.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Several reports have shown that modification of secreted cytokines to generate membrane-bound forms by adding transmembrane or GPI sequences can restrict cytokine activity to the site of injection and thus reduce systemic toxicity without compromising antitumor activity. 26,27 The antitumor activity of a membrane-bound IL-12 as a GPI-anchored form had been demonstrated in previous studies. 30,34 However, GPI-anchored protein had been shown to be spontaneously released from the cell membrane due to shedding or proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 94%
“…26 Several cytokines have been expressed on the surface of tumor cells as integral membrane proteins or as glycosylphosphatidylinositol (GPI)-anchored proteins by their conjugation, respectively, to a heterologous transmembrane domain sequence or GPI-anchored signal sequence. 27 In general, these membrane-anchored cytokines, including IL-2, IL-4, IL-12, IL-21, granulocyte-macrophage colony-stimulating factor, and tumor necrosis factor-α, retain their biological activity and effectively stimulate immune cells and elicit protective antitumor immunity. [28][29][30][31][32][33] As regards IL-12, the in vivo growth rate of tumors transduced with GPI-anchored IL-12 was significantly delayed and the selected tumor clones expressing GPI-IL-12 were completely eliminated.…”
Section: Introductionmentioning
confidence: 99%